"Dark Energy" May Not Exist -- Is the Rest Mass Immutable? -- "Empty Voids". Issue 1 (January 2021) - Guan, Zhong
Abstract: "God particle" is the source of the mass of substance, and due to its uneven distribution in space, when the extragalactic galaxies move backwards to the edge of the universe, the same in different position of interstellar galaxy will have different inertial mass, then because of the momentum conservation principle there must be the accelerated motion, and no need to assume the repulsive forces (called dark energy) between the galaxies. The related astronomical phenomena of dark matter (the mechanical mass grater than photometric mass) can also be explained by the uneven distribution of "god particles" in the universe. Exploring the details of the distribution of "god particles" in comic space, and whether the existence of a local region of space that does not contain "god particles"---called "Empty Void", and its conditions for formation, may be one of the most cutting-edge questions in future physics.